The Impact of Environmental Changes on the Growth and Development of Organisms - Bambang Kulup Karnoto (PT. Anagata Sembagi Education, 2025)
Environmental change is a critical external factor shaping organism growth and development. Increasing environmental instability has the potential to alter biological mechanisms through changes in physical conditions and ecological stressors. This study aims to examine the impact of environmental change on organism growth and development using a quantitative approach based on Structural Equation Modeling Partial Least Squares. Quantitative data were analyzed to test causal relationships between environmental change as an exogenous variable and organism growth and development as endogenous variables. The results indicate that environmental change has a significant effect on organism growth but exerts a negative effect on organism development. In addition, organism growth shows a positive effect on organism development. These findings suggest that growth may function as an adaptive response to environmental change, whereas developmental processes are more vulnerable to intense environmental pressures. This study contributes theoretically to understanding the structural relationship between environmental factors and biological processes, while also offering practical implications for environmental management and organism adaptation strategies under global environmental change.